Differential methods of cell lysis for protein profiling of Alexandrium sp. using 2D gel electrophoresis - Hamdan, Nurul Ashima; Mohammad Noor, Normawaty; Abd Hamid, Shafida; Md Zin, Noor Hasniza; Muhamad Bunnori, Noraslinda (2016)
Introduction: Protein profiling of harmful algae is an ongoing study where the latest analysis was conducted on A. minutum in 2015. It is a fundamental study where the protein expression of targeted species can be used to understand the biochemical pathway of selected proteins. Alexandrium spp. in Malaysia has the potential to cause massive blooming that brings harm to the aquatic ecosystem. Methods: In this experiment three methods of cell lysis were tested against A. leei isolated from Malaysian waters. Axenic culture of the sample was established in enriched seawater media (ESDK) with 12 hours of light and 12 hours of dark conditions. The sample was extracted during exponential phase (day 18) where the same amount of cells was collected via centrifugation. Same buffer was used for each technique of cell lysis in order to get the best protein profiles in terms of band or spot intensity and number. The cells of A. leei were lysed using sonication in ice-cold water bath, sonication with probe and freeze-thawing followed by sonication in iced bath. Conclusion: Nevertheless it can be concluded from the qualitative analysis using SDS-PAGE and 2D gel electrophoresis that freeze thawing mode of cell lysis produced excellent result among others as the protein spots produced were precise with less streaking observed.